Rhodium Nanoparticles as Precursors for the Preparation of an Efficient and Recyclable Hydroformylation Catalyst. Issue 10 (4th May 2015) - Garcia, Marco A. S.; Oliveira, Kelley C. B.; Costa, Jean C. S.; Corio, Paola; Gusevskaya, Elena V.; dos Santos, Eduardo N.; Rossi, Liane M.
Abstract Despite all the advances in the application of nanoparticle (NP) catalysts, they have received little attention in relation to the hydroformylation reaction. Herein, we present the preparation of a hydroformylation catalyst through the immobilization of air‐stable rhodium NPs onto a magnetic support functionalized with chelating phosphine ligands, which serves as an alternative to air‐sensitive precursors. The catalyst was active in hydroformylation and could be used in successive reactions with negligible metal leaching. The interaction between the rhodium NPs and the diphenylphosphine ligand was evidenced by an enhancement in the Raman spectrum of the ligand. Changes occurred in the Raman spectrum of the catalyst recovered after the reaction, which suggests that the rhodium NPs are precursors of active molecular species that are formed in situ. The supported catalyst was active for successive reactions even after it was exposed to air during the recycling runs and was easily recovered through magnetic separation.